A genealogy of hostility: parental alienation in England and Wales. Issue 1 (2nd January 2020) - Barnett, Adrienne
ABSTRACT: This article explores the emergence and development of parental alienation (PA) in England and Wales. It considers the background into which PA first appeared in private law proceedings concerning children in England and Wales, and examines how it progressed in the case law through the changing political and discursive context of private family law from 2000 to the end of March 2019. A clear pattern emerged of, initially, parental alienation syndrome and subsequently PA being raised in family proceedings and in political and popular arenas in response to concerns about and measures to address domestic abuse. The case law revealed a high incidence of domestic abuse perpetrated by parents (principally fathers) who were claiming that the resident parents (principally mothers) had alienated the children against them, which raises questions about the purpose of PA. More recently, a PA 'industry' appears to have amassed comprising experts, therapists and lawyers, advocating transfers of children's care from 'alienating' mothers to non-resident fathers, as well as PA therapy for children and parents. While PA has had a chequered history and is not without its critics, it has become part of the discursive repertoire of current family law, with increasingly harsh consequences for women and children.